(untitled) (Damu Journal of Sport Sciences, 2025)
The importance of research is to develop a rehabilitative program that includes repeated injuries to the cruciate ligament injury to the knee joint, which works to strengthen flexibility in gymnastics players, and helps the research to prepare a rehabilitative approach to rehabilitate flexibility in the knee joint for athletes with cruciate ligament injuries for the gymnastics event, knowing the effect of the rehabilitative approach to rehabilitate bending in the knee joint with the cruciate ligament. For gymnastics players. The researcher used the experimental method to suit the research method, and the research sample was 11 players with anterior cruciate ligament injuries. In addition to that, homogeneity and equivalence were violated, and the study concluded that the prepared program showed a clear improvement in motor range for the benefit of the second group, and that the rehabilitation program provided technology (such as electrical stimulation) and provided psychological support and follow-up for a period of 6-12 months after their return to sports.